Test-retest reliability and minimal detectable change of Dutch-Flemish Patient Reported Outcomes Measurement Information System (PROMIS®) Computerized Adaptive Tests for musculoskeletal disorders - R. M. Arensman; E. J. A. Haan; C. B. Terwee; J. van Rosmalen; H. Wittink; H. Kiers (PLoS ONE, 2025)
Objective To examine the test-retest reliability and minimal detectable change (MDC) of the Dutch-Flemish Patient Reported Outcomes Measurement Information System (DF-PROMIS) Pain Interference (PI) v1.1, Physical Function (PF) v1.2, and Upper Extremity (UE) v2.0 computerized adaptive tests (CATs) in patients with musculoskeletal conditions receiving physical therapy in primary care. Design Observational cohort study. Methods Patients with musculoskeletal conditions of the spine or upper extremity were recruited from fourteen physical therapy practices. Participants completed DF-PROMIS CATs at baseline and again three to fourteen days later. Test-retest reliability was evaluated using the intraclass correlation coefficient (ICC) (two-way random effects, absolute agreement) and minimal detectable change (MDC). Reliability at the participant-level was visually represented by plotting test-retest scores with corresponding 95% confidence intervals (CIs). Results Data from 225 patients were analyzed. The DF-PROMIS CATs demonstrated sufficient test-retest reliability, with ICC values ranging from 0.79 to 0.91. MDC values ranged from 4.80 to 6.08 across all measurements. Participant-level reliability was high (0.9–0.95) for most measurements but lower for scores further from the mean. The 95% CIs for test-retest measurements overlapped in 95.3% of measurement pairs. Conclusion The DF-PROMIS PF, UE, and PI domain CATs demonstrated sufficient reliability and precision in patients with musculoskeletal conditions receiving physical therapy in primary care practices. Future research should focus on implementing DF-PROMIS CATs in clinical practice, examining their responsiveness, and evaluating their feasibility. Adoption of DF-PROMIS domains as outcomes in intervention studies and clinical practice will enhance interpretability and comparability of results across different patient groups.